PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PEMBELAJARAN DARING MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN - Retno Dumila; Desrina Hardianti; Noprisa Noprisa (Hipotenusa Journal of Research Mathematics Education (HJRME), 2021)
This study aims to determine the improvement of students' mathematical communication skills in online learning by using instructional video media. The study used a quasi-experimental method with a pretest-posttest control group design. The research subjects were students of class VIII in a private Junior High School in Bandar Lampung City. There are two classes in this study, namely the experimental class consisted of 33 students and the control class consisted of 33 students. The experimental class received online learning using instructional video media, while the control class used the method without giving intructional videos. The research instrument used a mathematical communication ability test. The results showed that the inprovement in mathematical communication skills in the experimental class was better than the control class